SMART WHEEL: A COMMUNITY-DRIVEN NAVIGATIONAL APP FOR WHEELCHAIR DISABLED PEOPLE: A CASE STUDY ON IOI CITY MALL - MURUGAN, THURGASHHINI (IRC, 2020)
This paper offers a review on developing a mobile system on wheelchair disability in Malaysia shopping malls, especially to”create awarenession the importanceiofidisability toithe currentisociety. This idea was chosenidue toisome criticalisituationitoday where there is still a pervasive lack of access to mobility for people with disabilities, particularly in less-resourced settings. Despite the challenges of providing wheelchairs, the safety, jobs, social integration and life satisfaction benefits are obvious. To addressithis issue, my researchipaper focuses on coming up with a mobile navigation system which highlyiencourage wheelchair disability people to overcome their insecuritiesito travelialone and shows that wheelchair disability plays an important role in their physical activity and social involvement.”The main issue that this societyihas toiunderstand from this idea is that, travelling with disabled mobility has been relatively unexplored in Malaysia, but with high rising rates of disability and number of people, it is crucial to know what the most severed impaired people think of current system. In addition, this project’s goal is to achieve awareness of the problem among wheelchair inaccessible public places users. They should always be encouraged to think about and enhance their premises usability. Atitheiend of thisiproject development, iI hope that society are more aware on the disability consequences and the map contributes to an effective and flexible wheelchair environment.